2017
DOI: 10.1002/elsc.201700059
|View full text |Cite
|
Sign up to set email alerts
|

A novel protocol to prepare cell probes for the quantification of microbial adhesion and biofilm initiation on structured bioinspired surfaces using AFM for single‐cell force spectroscopy

Abstract: We present a novel protocol that uses single-cell force spectroscopy to characterize the bacteria-to-surface interactions involved in early steps of biofilm formation. Bacteria are immobilized as a monolayer by electrostatic interactions on a polyethyleniminecoated silica bead, and the Escherichia coli-bead complex is then glued on a tipless cantilever. We validated our new protocol by comparing to earlier published methods using single bacteria, but in contrast to these, which carry out bacterial attachment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…PEI, a positively charged polymer, adheres strongly to cells 67,68 . For that reason, it has been used in single cell force spectroscopy to attach bacteria on cantilevers 69 . A strong adhesion between PEI and HepG2 cells was also observed in our control experiments.…”
Section: Discussionmentioning
confidence: 99%
“…PEI, a positively charged polymer, adheres strongly to cells 67,68 . For that reason, it has been used in single cell force spectroscopy to attach bacteria on cantilevers 69 . A strong adhesion between PEI and HepG2 cells was also observed in our control experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This was further confirmed with tip decorated with milk proteins, the target of LGG pili for adhesion in dairy ( Guerin et al, 2018a , Guerin et al, 2018b ). Very different force distance signatures were obtained for the unfoding of pili from Gram-negative bacteria such as P. aeruginosa and E. coli ( Forero et al, 2006 , Beaussart et al, 2014a , Mulansky et al, 2017 ), resulting in plateaus preceded by a region of zero force, which are most likely due to a force-induced conformational changes within individual pili.…”
Section: Single-molecule Mapping On Microbial Surfacesmentioning
confidence: 99%
“…All these examples reveal the versatility of AFM-based SCFS to measure interactions between cells and substrates. Yet, as bacteria are small (usually at least one dimension < 1 µm), it has been stated that it is difficult to precisely position the cell at the apex of the cantilever and to avoid aspecific interactions coming from direct contact between the cantilever and the substrate ( Beaussart et al, 2014b , Mulansky et al, 2017 ). To overcome this limitation, the preparation of colloidal probes where silica spheres are glued to tipless cantilever is a good alternative ( Fig.…”
Section: Probing Microbial Adhesion At the Single-cell Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…These prior works have shown that bacteria immobilized on PEI-coated surfaces are very stable, adhering firmly in place and allowing a nano-sized cantilever to map its surface topography with very high spatial resolution—all under physiological conditions [ 9 , 17 , 19 ]. Moreover, PEI has been used to immobilize bacteria on micron-sized probes for force spectroscopy measurements, to quantify the extent of bacteria-surface interactions [ 20 ]. It is worth noting that the PEI-immobilized bacteria remained viable and did not show any structural changes of the outer membrane.…”
Section: Introductionmentioning
confidence: 99%